PENDIDIKAN NILAI DALAM PEMBENTUKAN KARAKTER - Abdul Wahab Syakhrani; Halipatun Nisa; Munazatul Karimah; Nadia Hafizah; Nadia Ulfah; Najwa Sifa (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
Values and character are two interconnected pillars in the development of an individual, where values serve as internal principles and character represents their manifestation in daily actions. Education should not be limited to the understanding of moral concepts but must also involve the internalization and habituation of values to build strong and integrated character. The success of character formation is a collective responsibility involving family, teachers, and society. Parents act as the primary foundation, teachers as role models and sources of inspiration, and society as a reinforcing environment for positive values. In the face of globalization and rapid technological advancement, character education becomes essential in maintaining identity, enhancing critical thinking, and fostering empathy and morality in social life.